MAQHASID AS-SYARIAH DAN QISHAS: PEMIKIRAN AS-SYATIBI DALAM KITAB AL-MUWAFAQAT - Suyitno . (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
Qisas is a legal practice that there is a pre - Islamic and Islamic modified in the future. However, in modern times it appears aspiration rejection of the law of Qisas in the name of human rights. Even among Muslims themselves also occur on the grounds that rejection that Qisas has violated maqashid al - Shari'ah ie hifzh al - nafs (keep soul). Therefore, through this paper, the author tries to examine in depth the problems with the approach maqashid al - Shariah are summarized in detail in the book of al - Muwafaqat work of al - Syathibi.